Experiences of pregnant women and healthcare professionals of participating in a digital antenatal CMV education intervention. (March 2022) - Montague, Amy; Vandrevala, Tushna; Calvert, Anna; Yeh, I-Ling; Star, Caroline; Khalil, Asma; Griffiths, Paul; Heath, Paul T.; Jones, Christine E.
Abstract: Objective: The study aimed to explore the perspectives of participating pregnant women and Health Care Professionals (HCPs) towards receiving and providing cytomegalovirus (CMV) education so that barriers and facilitators towards incorporating CMV in routine antenatal care could be better understood. Design: This process evaluation phase employed a qualitative design using individual, semi-structured, face-to-face interviews. Setting: Recruitment and interviews took place within a large teaching hospital from an ethnically diverse area of South-west London Participants: The study sample included 20 participants: 15 pregnant women, and five HCPs. All participants were involved in a single centre randomized controlled trial of a digital CMV educational intervention in pregnancy. Findings: Pregnant participants expressed a strong desire to receive information about CMV as part of routine antenatal care. Although HCPs were accepting of the need for CMV education, it was evident that they felt unequipped to provide this; reasons included lack of time, uncertainty about clinical pathways and concern about the potential emotive impact of CMV education. Pregnant women suggested that expressing behaviour changes as risk reduction rather than prevention, made the behaviours feel more achievable and realistic. The support of partners was considered a key factor in the successful adoption of behavioural changes by pregnant women. Key conclusions and implications for practice: There is an onus on HCPs to consider how CMV can be included as part of antenatal education, with messaging framed as risk reducing rather than prevention.